Overproduction and properties of lipase by a wild strain of Burkholderia lata LBBIO-BL02 using chicken fat - Oliveira, Bruno H. [UNESP]; Santos, Rachid É. [UNESP]; Loiola, Luiz E. A. [UNESP]; Nascimento, Valeria M. G. [UNESP] (Springer Nature, 2015)
In this work, we report the overproduction of lipases by a new wild strain of Burkholderia lata (LBBIO-BL02) in submerged fermentation to seek an economically attractive bioprocess. The best fermentation medium composition was containing chicken fat (12.5 mL/L) and ammonium phosphate (15 g/L) at 35 ºC and pH 7.0, resulting in a lipase titer of 1137.82 U/mL and 2146.83 U/mg. The lipase characterization exhibited maximum activity at 55 °C and pH 8.0. The lipase retained 100, 93 and 85 % of its maximum activity at 45, 50 and 60 °C, respectively, and 78, 82 and 100 % at pH 2.2, 3 and 10, respectively. The enzyme was successfully immobilized on Celite by adsorption and showed a promising future for various organic syntheses because of its stability in organic solvents. All the results shows that Burkholderia lata LBBIO-BL02 is a superior lipase-producing bacterium and its enzyme showed good potential for industrial and biotechnology application.
Keywords: Bioprocess design; Celite; Chicken fat; Immobilization; Lipase; Overproduction